1996
DOI: 10.1021/ac960119j
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Diffusion of Molecules Partitioned into Silica-Bound Alkyl Chains:  Influence of Chain Length and Bonding Density

Abstract: Lateral diffusion of a hydrophobic fluorescent molecule partitioned into monomeric alkyl chains bound to a planar silica substrate was measured as a function of chain density and chain length. Measurement of fluorescence recovery after patterned photobleaching was used to observe the diffusional relaxation of a concentration profile of probe molecules over distances of micrometers. The diffusion rate of the probe molecule partitioned into C-18 chains decreased with decreasing chain coverage. As the chain lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 59 publications
0
29
1
Order By: Relevance
“…A comparative study [164] has reported the short range effect of run time on the column parameter of different high or low grafted reversed phases. In order to assert that C22 and C30 bondages give best peak symmetry, they must be evaluated with the same based silica, the same bondage density [168] and in such a way that the stereochemical state of the stationary phase is the same, i.e. Thus, it can be argued that longer alkyl chains will interact preferentially with each other, forming overlapping chains that restrict the access of the surface silanols [165,166].…”
Section: 22amentioning
confidence: 99%
“…A comparative study [164] has reported the short range effect of run time on the column parameter of different high or low grafted reversed phases. In order to assert that C22 and C30 bondages give best peak symmetry, they must be evaluated with the same based silica, the same bondage density [168] and in such a way that the stereochemical state of the stationary phase is the same, i.e. Thus, it can be argued that longer alkyl chains will interact preferentially with each other, forming overlapping chains that restrict the access of the surface silanols [165,166].…”
Section: 22amentioning
confidence: 99%
“…[9][10][11] Lateral diffusion is measured very accurately by either fluorescence recovery after photobleaching [4][5][6][7][8][12][13][14] or fluorescence correlation spectroscopy, [15][16][17][18] where the latter avoids perturbing the sample. The interpretation of the results is most straightforward when there is a single diffusing species; however, the data can, in principle, be analyzed for multiple species.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding retention in RPLC and its dependence on conformational order, in general, the highest degree of shape selectivity [16,47,48] and retention [49,50] are observed for the most ordered stationary phase. However, controversy can also be found with respect to this issue.…”
Section: Resultsmentioning
confidence: 97%